Epilepsy perception amongst education professionals - Lunardi,Mariana dos Santos (2012)
INTRODUCTION: Epilepsy is a prevalent neurological disorder that may cause school failure due to several factors such as seizure severity, lack of information about the condition and stigma. This study aimed to evaluate the degree of perceived stigma and knowledge towards epilepsy among education professionals, and additionally, provide them correct information about epilepsy to reduce stigma through a training course. METHODS: Social and demographic data, as well as the degree of stigma were obtained through the Stigma Scale of Epilepsy. To estimate the level of educational professionals' knowledge about epilepsy we used the Questionnaire about Epilepsy. Statistical analysis consisted of Pearson's or Spearman's correlation tests for numerical parametric or non-parametric variables were used to determine potential significant associations. A p <0.05 was considered significant. RESULTS: Two hundred and twenty-five education professionals were interviewed in three different cities in Southern Brazil. Approximately 65% of subjects would attempt to open the mouth of a student during a seizure and the stigma measured by Stigma Scale of Epilepsy before the course was 45.4±16.61. CONCLUSION: The data indicate that education professionals have partial knowledge about epilepsy and a short duration course would be able to improve it and reduce its stigma in this population.